OPTIMIZING SALES CONVERSION AND CUSTOMER RAPPORT IN RESPONSE TO SHOPEE ONLINE SHOPPING APP: NLP RAPPORT BUILDING TECHNIQUES - Aynen Kresensia Br Sembiring; Rita Hartati; Adam Syahdani; Nael Simarmata; Nindi Tri Utami; Novita Sari Hutapea (Bajang Institute, 2024)
The Shopee Online shopping application is one proof of the advancement of technology today, from the application we can shop without having to go to the location directly. Therefore, the online application certainly has advertisements to attract buyers and build good relationships. Moving on from this, this research will examine the advertising language used, whether using Neuro-Linguistic Programming techniques in building good relationships, and increasing sales conversions. The research method used in this research is qualitative, textual, and analytical, which collects data in the form of Shopee promotional advertisements, and analyzes the language used. From the research that has been carried out, it is found that the advertising language used in the Shopee online shopping application uses neuro-Linguistic programming and builds good relationships and attracts buyers